TEXTBOOK AND ENGLISH TEACHER IN JUNIOR HIGH SCHOOL - Ridha Fadilah; Ariati Mufidah (Intensive Journal, 2021)
This research is intended to describe of the role of the textbook in English class. The subject of the study was English teachers in state junior high school in Banjarmasin. Data were collected through interviews, class observation, and document analysis. The investigation found that the teachers considered the textbook both central and external books helped them in preparing the lesson. They used several strategies to adapt the textbook by adding the material and modifying the task in the book. There were three main problems faced by English teachers at state junior high school 23 Banjarmasin, limited supported kits from the book, lacks materials inside the textbook, and high language level for students used in the book. However, this research is essential to conduct to present the real situation that happened in the English classroom.